Konstruksi Gender Dalam Relasi Intimate Relationship Pada Novel Friendzone: Lempar Kode Sembunyi Hati Karya Alnira (Sebuah Analisis Framing) - Ratna Wati; Nunik Hariyani; Veny Ari Sejati (IKIP Budi Utomo Malang, 2020)
This thesis is titled Gender Construction in Intimate Relationship on “Friendzone: Lempar Kode Sembunyi Hati” Novel by Alnira (A Framing Analysis). The purpose of this research is to find the expression of feelings between men and women in intimate relationships through the novel characters, and discover the relationships that exist between gender construction and intimate relationships through the analysis of the Gamson and Modigliani framing models. This research uses descriptive qualitative method, where the data presented, are not in the form of numbers and more emphasis on meaning rather than generalization. Data collection techniques used are using documentation techniques and unobtrusive observation techniques, where this technique is a technique used to examine texts, and audio-visual recordings. This research was conducted during the 2019 October to January 2020. The research object is the novel “Friendzone: Lempar Kode Sembunyi Hati” by Alnira, that released on February 2018 with 300 pages. Then the object is dissected using the Gamson and Modigliani Framing analysis model to see how the expression of feelings constructed by gender in Dira and Ransi characters on the novel. The results of this research are, gender can affect the expression of a man and woman in expressing their feelings, where men express their feelings through gestures and non-verbal actions, while women need a recognition of the status of the relationship through their verbal. In addition, gender construction will influence the success of intimate relationships between men and women, if misunderstandings that occur due to differences in conversation patterns can be resolved.